Enhancing Restorative Justice through Victim and Witness Protection Measures - Sayyed, Hifajatali; Kaushik, Kriti (Jurnal Cita Hukum, 2024)
This research explores the pivotal role of victim and witness protection measures in augmenting the principles and effectiveness of restorative justice. Restorative justice, as a paradigm, seeks to address the harm caused by criminal behaviour by involving all relevant parties in a collective and participatory resolution process. The well-being and cooperation of victims and witnesses are critical for the success of restorative justice initiatives. This study investigates how comprehensive protection measures contribute to creating a supportive environment, fostering trust, and facilitating the engagement of victims and witnesses in the restorative justice process. The analysis encompasses various victim and witness protection aspects, including physical safety, emotional well-being, and legal considerations. By examining existing programs and policies, the research identifies best practices and areas for improvement in ensuring the security and confidentiality of those participating in restorative justice proceedings. Additionally, the study assesses the impact of protection measures on the willingness of victims and witnesses to actively participate, share their perspectives, and collaborate towards achieving meaningful resolutions. Ultimately, this research aims to provide insights and recommendations for policymakers, practitioners, and scholars to enhance the integration of victim and witness protection measures within restorative justice frameworks. By prioritising the safety and support of individuals involved, the justice system can better fulfil its commitment to addressing harm, promoting accountability, and fostering healing within communities affected by criminal acts.